Impact of an EMR-Based Daily Patient Update Letter on Communication and Parent Engagement in a Neonatal Intensive Care Unit - Palma, Jonathan P. (2012)
OBJECTIVE: To evaluate the impact of using electronic medical record (EMR) data in the form of a daily patient update letter on communication and parent engagement in a level II neonatal intensive care unit (NICU). STUDY DESIGN: Parents of babies in a level II NICU were surveyed before and after the introduction of an EMR-generated daily patient update letter, Your Baby’s Daily Update (YBDU). RESULTS: Following the introduction of the EMR-generated daily patient update letter, 89% of families reported using YBDU as an information source; 83% of these families found it “very useful”, and 96% of them responded that they “always” liked receiving it. Rates of receiving information from the attending physician were not statistically significantly different pre- and post-implementation, 81% and 78%, respectively (p = 1). Though there was no statistically significant improvement in parents’ knowledge of individual items regarding the care of their babies, a trend towards statistical significance existed for several items (p <.1), and parents reported feeling more competent to manage information related to the health status of their babies (p =.039). CONCLUSION: Implementation of an EMR-generated daily patient update letter is feasible, resulted in a trend towards improved communication, and improved at least one aspect of parent engagement—perceived competence to manage information in the NICU.